The variation of the levels of anxiety and motivation depending on the use of different written tasks - Fuentes Rojas, Patricia (Universidad de Santiago de Chile, 2023)
Integrantes: Patricia Fuentes Rojas, Melanye Padilla Muñoz, Francisca Pavez Tapia, Valeria Pinto Celis
Keywords: Inglés - Enseñanza - Hablantes extranjeros; Estudiantes de educación media - Actitudes; Motivación en la educación - Chile